Book review of: "Western Tchoukoutou", by Florent Couao-Zotti (Benin) - Kohnert, Dirk (My University, 2020)
A new star has opened in the sky of authors from Francophone Africa. So far, he is hardly known outside of the language area of the Francophonie. His name is Florent Couao-Zotti and he comes from Benin, West Africa. Couao-Zotti develops in 18 episodes, one crazier than the other, literally a fabulous story. The Académie française awarded him the prestigious 'Prix Roland De Jouvenel ' for his novel 'Western Tchoukoutou' published by Gallimard in 2018. It would be in the English reader’s best interest that the novel will soon find a publisher who translates the book into English, not least so that the readers of neighboring Anglophone Africa can enjoy this marvelous taste of new African literature.
Keywords: African Literature; African Studies; Benin; Book review; Contemporary fiction; Littérature Francophone; West Africa